Interdisciplinary higher education perspectives and practicalities - Davies, Martin; Devlin, Marcia; Tight, Malcolm (International perspectives on higher education research ;, 2010)
Interdisciplinary Higher Education offers a contemporary of our understanding and practice of interdisciplinary higher education. Part I (Chapters 1 to 5) considers a range of theoretical perspectives on interdisciplinarity: the nature of disciplines, complexity, leadership, group working, academic development. Part II (Chapters 6 to 18) provides more than a dozen vignettes of interdisciplinary practice, drawn from Australia, Malaysia, the Netherlands, New Zealand and the United Kingdom.